But I AM normal: safe? driving in Vietnam. Issue 2 (13th April 2015) - Hue, Duong Trong; Brennan, Linda; Parker, Lukas; Florian, Michael
Abstract : Purpose: – This paper aims to elucidate perceptions of safe driving and social norms in relation to driving motorbikes in the Vietnamese context. Design/methodology/approach: – A series of focus groups was undertaken in relation to driving practices from a number of groups: adolescents, families and adult males and females. The discussion centred on how driving behaviours were socialised within the various groups. Findings: – The research highlighted some very interesting social dynamics in relation to how safe driving habits are established and supported within the social context. In particular, the separation of descriptive and injunctive norms and the role such norms play in socialising driving behaviours, safe or otherwise. Practical implications: – The implications for social marketing practice are considerable, especially in the Vietnamese context where injunctive norms are difficult to portray, given the dynamics of the media landscape. Social marketing campaigns will need to have a broader consideration of how to establish descriptive norms, bearing in mind the social milieu in which the behaviours occur. Originality/value: – This research is the first of its kind in the Vietnamese context. While much practice-led innovation is occurring in the region, there is little extant research on the topic of social norms and the socialisation of behaviours within the Southeast Asian region.